Support or suppress: Father’s parental leave uptake in the private-sector workplace context in Finland - Chapman, Simon N.; Kotimäki, Sanni; Helske, Satu; Hägglund, Anna Erika (Cambridge University Press (CUP), 2026)
The Finnish parental leave system has undergone numerous reforms to encourage fathers’ leave uptake, in part to redress unequal divisions of early childcare, yet many fathers have not taken full advantage of it. Leave is usually taken from the workplace, and though workplace factors are often cited as typical barriers to uptake, they remain understudied compared to policy and individual-level motivators. We systematically investigated the association of important workplace structural characteristics and parental leave decisions of private-sector-employed first-time fathers in 2013–2017, using Finnish register data and a multilevel Bayesian approach. While the probability of taking father’s quota varied by workplace gendered structures and competitiveness, these differences were due to the selection of fathers into workplaces on individual-level characteristics, rather than resulting from differing workplace structures. Workplace educational level was important, but only for tertiary-educated fathers: highly-educated fathers in low-educated environments were less likely to take longer leaves, suggesting that replaceability may be the main mechanism behind the differences. These findings suggest that differing workplace contexts have less to do with structural factors than with workplace cultures and fathers’ individual situations, calling for further study on the interplay of individual and contextual factors in usage of paternal leave entitlements.